Optimal Financial Crises - Allen, Franklin; Gale, Douglas (Journal of Finance, 1998)
ABSTRACT Empirical evidence suggests that banking panics are related to the business cycle and are not simply the result of “sunspots.” Panics occur when depositors perceive that the returns on bank assets are going to be unusually low. We develop a simple model of this. In this setting, bank runs can be first‐best efficient: they allow efficient risk sharing between early and late withdrawing depositors and they allow banks to hold efficient portfolios. However, if costly runs or markets for risky assets are introduced, central bank intervention of the right kind can lead to a Pareto improvement in welfare.